RANCANG BANGUN WEBSITE PENDATAAN HIMPUNAN MAHASISWA SERUYAN BERBASIS SMS BROADCAST - Parhusip, Jadiaman; Sahay, Abertun Sagit; Safi’i, Muhammad Sabrin (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2018)
Seruyan student association is one of student organization in Palangka Raya. It isfound that information of Seruyan students lacks enough data. It becomes a problem for theofficer since the officer has to come every campus, boarding house or house to complete thedata manually. It consumes too much time to collect and process the data. This designedwebsite is hoped can help the officer collecting, managing, and informing those students’data easily. It is hoped that this website which is developed using SMS Broadcast can be veryhelpful in speed and quality for presenting the information. This kind of website also offer astructured storage. Besides, available information then can be accessed in an unlimitednumber of times and places.This research is conducted using PHP language programme and MySQL database. Theresearcher also uses a methodology of software development which known as waterfallmethodology (Analysis, Design, Code, Testing and Maintenance). Besides, ContentManagement System (CMS) is also used to manage content of the website includes commandto add, change, and delete data which can be accessed from the administrator system page.This website is tested using whitebox technique which also includes a test for visitor,member, administrator, and browser. In the other opportunity in the future, it is hoped thatthis website can be developed bu adding some other features such as discussion forum orchat room.